UMKM Survival Strategy During the Covid-19 Pandemic (Case Study in Kota Bengkulu) - Sari Nurrohmah Yuniarta; Lilis Kurniati; Rizando Purga; Miti Yarmunida; Amimah Oktarina (Penerbit Jurnal Indonesia, 2021)
Usaha micro small and medium (MSMEs) Indonesia paralyzed duringthe Covid-19 pandemic. This is due to government policies in controlling Covid-19 that interfere with MSME activities. As a result, the income of small and medium-sized and micro businesses decreased. Small and medium-sized micro-businesses are in decline. You have to deal with this situation if you want to survive. The purpose of this study is to find out how micro small and medium enterprises (MSMEs) strategies can survive the Covid-19 pandemic. This research is carried out with qualitative research. This type of research is a descriptive data collection method that uses structured and gradual interviews. The results of direct observations showed that during the covid-19 pandemic, MSMEs implemented various strategies to maintain business continuity, namely, product and service quality improvement strategies, product strategies, price strategies, and also promotional strategies. MSME actors must also provide friendly service to customers and quality products, so that consumers can trust or choose good product quality.